Analisis Laporan Keuangan: Studi Pada PT. Japfa Comfeed Indonesia Tbk Tahun 2020-2022 - Vania Palidita Febriana; Wulandari, Tiara Suci (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This article aims to analyze PT's financial reports. Japfa Comfeed Indonesia Tbk. The object of the study is PT's financial statements. Japfa Comfeed Indonesia Tbk for the years 2020-2022 includes the balance sheet, income statement, and cash flow statement. A descriptive approach is carried out using financial ratios. This analysis involves measuring the company's performance based on four main aspects: liquidity, solvency, profitability, and activity. The research findings show that PT. Japfa Comfeed Indonesia Tbk has good financial performance during the analysis period. The calculation results using the liquidity ratio show that the company can meet its short-term obligations fairly well. This indicates that the company can effectively manage its current assets to pay debts due shortly. The solvency ratio shows that the company has a balanced leverage ratio between debt and equity, allowing it to bear the debt burden without negatively impacting its financial stability. Furthermore, the profitability ratio shows that the company can consistently generate income during the analysis period, which indicates the company's effectiveness in allocating costs and income to achieve profits. The overall results of this analysis show that the company's resources are used efficiently and effectively